Planeamento e Periodização, em equipas profissionais, na perspetiva do Treinador de elite - Carvalho, Gonçalo (2019)
The main goal of any coach is the achievement of success, materialized through the achievement of the goals that he proposes and in the collective dynamic he creates in his team. To make this possible, it is necessary that he designs, plans and performs quality work in order to allow an adequate intervention with the players. In this framework, concepts such as Planning, Periodization, Game Model, Principles and Dimensions of Training and Sports Performance are of vital importance in the coach's action. The present study aimed to understand the principles of training in the perspective of some elite national coaches in the context of professional football, identify the coaches’ options/decisions when planning and through the sports season. It is also our intention to collect data and information regarding this problematic that can contribute to the creation of a tool which represents the training conception mentioned above. To carry out the study, ten interviews were conducted with soccer coaches, with professional experience in men's senior teams, competing in the main Portuguese championships (Liga NOS - 1st league, Ledman Liga Pro - 2nd league). The answers were treated qualitatively, and the information was coded and analyzed in the software MAXQDA 2018®. The information analysis allowed us to realize that: the Training Process is seen by coaches as comprehensive and fundamental; there is a concern to schedule adequately and on a weekly basis; the Game Model discloses an idea, is dynamic and worked from the first day, taking into account the constituent players of the squad; the Training Model and the Game Model are interconnected and seek a constant good performance; the microcycles are a type structure, with complex training units, intense exercises and with well-defined objectives; coaches are given the importance of evaluating and controlling the training. We believe that coaches, in their daily and professional function, rely on theories and beliefs, thoughts and interactive decisions when making routine, immediate and reflexive decisions